2022
DOI: 10.1002/jmv.27942
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic in Southern Brazil: Hospitalizations, intensive care unit admissions, lethality rates, and length of stay between March 2020 and April 2022

Abstract: Coronavirus disease 2019 (COVID‐19) pandemic spread rapidly with more than 515 million cases and 6.2 million deaths. Epidemiological factors are important for understanding the state of the pandemic. This study aims to evaluate the hospitalizations, intensive care unit (ICU) admissions, and lethality from March 2020 to April 2022. Data were collected from a hospital in Porto Alegre city, southern Brazil. The Mann–Whitney, analysis of variance, and Kruskal–Wallis tests were used to compare quantitative variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…More precisely, the awareness of the negative consequences when not acting pro-socially by vaccination was related to individuals' care for other's welfare and the maintenance of peaceful relationships with others. This was consistent with earlier research conducted [31,34], on the link between altruistic values and pro-social behavior during threatening situations. However, while other values positively influence the promotion of prosocial vaccination behavior, traditional values have the opposite effect of what was anticipated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More precisely, the awareness of the negative consequences when not acting pro-socially by vaccination was related to individuals' care for other's welfare and the maintenance of peaceful relationships with others. This was consistent with earlier research conducted [31,34], on the link between altruistic values and pro-social behavior during threatening situations. However, while other values positively influence the promotion of prosocial vaccination behavior, traditional values have the opposite effect of what was anticipated.…”
Section: Discussionsupporting
confidence: 92%
“…This rationale has been supported empirically by evidence on the association between commonality and the readiness to self-isolate to protect others in the event of a pandemic supports. For instance, Wolf and his colleagues discovered that values, such as benevolence are crucial in promoting prosocial pandemic-related behavior (e.g., social distancing) [34]. Furthermore, it appears that communal personality traits are associated with higher compliance behavior [35].…”
Section: Awareness Of Consequences and Valuesmentioning
confidence: 99%
“…The ICU setting has been investigated less widely and is probably the one with the greatest impact from the pandemic because the care needs of patients with SARS-CoV2 infection and severe respiratory failure forcibly have involved the ICUs on the front line, with a limitation of beds available for other diseases, including stroke. 4 , 5 In this setting the patients with stroke who are admitted in ICU have a worse prognosis in comparison with the prepandemic data, as reported by Ranzani et al 6 with a clear link between the rise in COVID-19 cases and the increased mortality rate. These data interrupted a trend of improvements in survival rates over 10 years, thereby confirming the analysis of hospital metrics in a single Brazilian hospital.…”
mentioning
confidence: 81%
“…These data interrupted a trend of improvements in survival rates over 10 years, thereby confirming the analysis of hospital metrics in a single Brazilian hospital. 5 In this issue of CHEST , a retrospective analysis of the first 250,000 hospital admissions for COVID-19 in Brazil showed that overall ICU admissions were 39% of all hospitalized patients with COVID-19, with an ICU mortality rate of 55%, and were 14% of the patients who underwent invasive mechanical ventilation outside the ICU. 7 …”
mentioning
confidence: 99%
“…Brazil is the Latin American country with the largest number of deaths due to COVID-19 recording more than 37 million reported cases and 699,000 deaths 2 . COVID-19 is a disease of public importance in southern Brazil, causing a lethality rate higher than 30% in the ICU and occupancy rates ranging from 79.1% to 91.6% during the pandemic period 3 . Additionally, readmissions in ≤ 30 days may occur frequently, with the respiratory cause being the main one 4 .…”
Section: Introductionmentioning
confidence: 99%